The Use of Hyperbaric Oxygen Therapy and Corticosteroid Therapy in Acute Acoustic Trauma: 15 Years' Experience at the Czech Military Health Service - Holy, Richard; Zavazalova, Sarka; Prochazkova, Klara; Kalfert, David; Younus, Temoore; Dosel, Petr; Kovar, Daniel; Janouskova, Karla; Oniscenko, Boris; Fik, Zdenek; Astl, Jaromir (International journal of environmental research and public health, 2021)
BACKGROUND: Acute acoustic trauma (AAT) ranks, among others, as one common cause of inner ear function impairment, especially in terms of military personnel, who are at an increased exposure to impulse noises from firearms. AIM OF THIS STUDY: 1. We wanted to demonstrate whether early treatment of AAT means a higher chance for the patient to improve hearing after trauma. 2. We find the answer to the question of whether hyperbaric oxygen therapy (HBO2) has a positive effect in the treatment of AAT. METHODS: We retrospectively analyzed data for the period 2004-2019 in patients with AAT. We evaluated the therapeutic success of corticosteroids and HBO2 in a cohort of patients with AAT n = 108 patients/n = 141 affected ears. RESULTS: Hearing improvement after treatment was recorded in a total of 111 ears (79%). In terms of the data analysis we were able to ascertain, utilizing success of treatment versus timing: within 24 h following the onset of therapy in 56 (40%) ears-54 (96%) ears had improved; within seven days following the onset the therapy was used in 55 (39%) ears-41 (74%) ears had improved; after seven days the therapy started in 30 (21%) ears-16 (53%) ears had improved. Parameter latency of the beginning of the treatment of AAT was statistically significant (p = 0.001 and 0.017, respectively). The success of the medical protocols was apparent in both groups-group I (treated without HBO2): n = 61 ears, of which 50 (82%) improved, group II (treated with HBO2): n = 73 ears, of which 56 (77%) improved. Group II shows improvement at most frequencies (500-2000 Hz). The most serious sensorineural hearing loss after AAT was at a frequency of 6000 Hz. CONCLUSION: Analysis of our data shows that there is a statistically significant higher rate of improvement if AAT treatment was initiated within the first seven days after acoustic trauma. Early treatment of AAT leads to better treatment success. HBO2 is considered a rescue therapy for the treatment of AAT. According to our recommendation, it is desirable to start corticosteroid therapy immediately after acoustic trauma. If hearing does not improve during the first seven days of corticosteroid therapy, then HBO2 treatment should be initiated.
Keywords: hyperbaric oxygen therapy; tinnitus; Humans; retrospektivní studie; Hearing Loss, Noise-Induced; nedoslýchavost z hluku; vojenský zdravotní systém; Military Health Services; Czech Republic; noise induced hearing loss; Retrospective Studies; Hyperbaric Oxygenation; Adrenal Cortex Hormones; hormony kůry nadledvin; Česká republika; acute acoustic trauma; hyperbarická oxygenace; lidé